(untitled) (In Factis Pax: Journal of Peace Education and Social Justice, 2011)
English Abstract: In spite of its geographic location, cultural diversity and marked development, the Department of Antioquia, has not been oblivious to the social and economic processes which have historically characterized Colombia. Such processes include the various situations of violence and violations of human rights occurring since the beginning of the “victims repair process” in the 1990s after the first demobilization of illegal armed groups. Consequently, further efforts by the Academy are required to help in the understanding of violence and aggressive behaviors. Simultaneously, further efforts are also required of the Governor Office in the designing of strategies in education and construction of peace. Previous efforts have been fruitful; human Rights reports conducted by various national and international NGOs note how the Department of Antioquia has shown significant progress, mainly in the reduction of violations of human rights violations as well as in the implementation of actions aimed at violence prevention. None the less, Antioquia is still characterized as one of the most violent departments of Colombia with the highest proportion of human rights violations at the national level. Given this background, the departmental government has included prevention of violence and education on peace as an essential program in its Development Plan. The mission of the program is to increase the skills of leaders at the local level, to raise awareness and educate their communities, in order to prevent and control the different factors of risk that generate any kind of violence at familiar, school or community-levels. In practice, the peace component is strongly linked to sub-regional development plans, and is promoted through interventions on prevention violence based on scientific evidence by the departmental government and University, seeking to foster coexistence among communities through training and education processes in education on peace and prevention of violence.